A Bird’s-Eye View: Student Insights on Auditors and the Auditing Profession - Khadija Hamed AL Hashimi; Rahaf Salman AL Mazidi; Mohammed Muneerali Thottoli (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
How students see auditing is essential since it may significantly affect their comprehension and interest. Stereotypes about auditors are influenced by their experience and proximity. To influence an auditor's attitudes and impressions of the auditee, proximity—including physical and psychological aspects—is essential. While negative perceptions might impede learning and make students uninterested, a positive view can increase student engagement and improve learning results. Perceptions can affect students' career decisions and how well they understand the role and significance of auditing in the business sector. This study looks into how students in Oman perceive auditing and how they develop preconceived notions about auditors based on proximity and expertise. The data was gathered using a questionnaire survey completed by 138 University students across the Sultanate of Oman. The researchers analyzed the data using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The study's findings show a significant relationship between students' decisions to pursue careers in auditing and how they see the auditing profession. The results, however, point to no relationship between auditors' perception and the auditing profession's choice. Moreover, there is no relationship between auditors' work and the student's decision to pursue auditing as a career.